THE EFFECT OF ACHIEVEMENT MOTIVATION TRAINING ON IMPROVING WOMEN ENTREPRENEURS MOTIVATION SAMBAS DISTRICT - Raziki Waldan (Raheema, 2020)
effect of Achievement motivation training on improving the achievement motivation of Women Entrepreneurs in Sambas Regency. This research is quasi-experimental, research subject, Sambas Regency Women Entrepreneurs. This study uses population research as a research subject, so this study uses all members of the population as research subjects. The research instrument used a questionnaire of 30 items and had been tested for validity and reliability. The data analysis technique used SPSS 20. The results of the study after the Women Entrepreneurs were given achievement motivation training results obtained 5 Women Entrepreneurs with low motivation criteria, 29 Women Entrepreneurs with moderate motivation criteria and 14 Women Entrepreneurs with high achievement motivation criteria. Based on the results of the posttest, it can be seen that there is a decrease in the number of women entrepreneurs who have low achievement motivation from 19 women entrepreneurs to 5 women entrepreneurs, on the contrary, there is an increase in the number of women entrepreneurs who have a moderate achievement, from 21 women entrepreneurs to 29 women entrepreneurs. Criteria for Women Entrepreneurs High achievement motivation also increased from 8 women entrepreneurs to 14 women entrepreneurs. Keyword: Achievement Motivation Training, Woman Entrepreneurs ABSTRAK Penelitian ini bertujuan untuk menentukan efek dari pelatihan motivasi prestasi dalam meningkatkan motivasi pencapaian wirausahawan perempuan di Kabupaten Sambas. Penelitian ini adalah kuasi-eksperimental, subyek penelitian, pengusaha perempuan Kabupaten Sambas. Studi ini menggunakan penelitian populasi sebagai subyek penelitian, jadi studi ini menggunakan semua anggota dari populasi sebagai subyek penelitian. Instrumen penelitian menggunakan kuesioner 30 item dan telah diuji untuk validitas dan kehandalan. Teknik analisis data yang digunakan SPSS 20. Hasil penelitian setelah pengusaha perempuan diberi hasil pelatihan motivasi prestasi yang diperoleh 5 perempuan pengusaha dengan kriteria motivasi rendah, 29 perempuan pengusaha dengan kriteria motivasi moderat dan 14 perempuan pengusaha dengan kriteria motivasi prestasi tinggi. Berdasarkan hasil posttest, dapat dilihat bahwa ada penurunan jumlah perempuan pengusaha yang memiliki motivasi prestasi rendah dari 19 perempuan pengusaha menjadi 5 perempuan pengusaha, sebaliknya, ada peningkatan jumlah perempuan pengusaha yang memiliki prestasi moderat, dari 21 perempuan pengusaha menjadi 29 perempuan pengusaha. Kriteria untuk perempuan pengusaha prestasi tinggi motivasi juga meningkat dari 8 perempuan pengusaha menjadi 14 perempuan pengusaha. Kata kunci: pelatihan motivasi prestasi, perempuan pengusaha